2015
DOI: 10.1007/s00125-015-3698-1
|View full text |Cite
|
Sign up to set email alerts
|

Early glycaemic control in metformin users receiving their first add-on therapy: a population-based study of 4,734 people with type 2 diabetes

Abstract: Aims/hypothesis The aims of this work were to assess glycaemic control in metformin users receiving their first add-on glucose-lowering therapy and to examine the real-life effectiveness of different add-on drugs. Methods We carried out a population-based cohort study using healthcare databases in northern Denmark during 2000-2012. We included 4,734 persons who initiated metformin monotherapy and added another glucose-lowering drug within 3 years. Attainment of recommended HbA 1c goals within 6 months of add-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 8 publications
3
35
1
2
Order By: Relevance
“…Thomsen et al 7 also noted that the threshold for intensification had fallen over the years, from about 8.8% in 2000-3 to about 8.1% in 2010-12 (estimated from graph in supplementary material; figure 3). If this has also occurred in the UK, it reinforces the need to be selective in extracting effect sizes for modelling.…”
Section: Triple Therapymentioning
confidence: 97%
“…Thomsen et al 7 also noted that the threshold for intensification had fallen over the years, from about 8.8% in 2000-3 to about 8.1% in 2010-12 (estimated from graph in supplementary material; figure 3). If this has also occurred in the UK, it reinforces the need to be selective in extracting effect sizes for modelling.…”
Section: Triple Therapymentioning
confidence: 97%
“…GLP-1 RAs are broadly recommended as add-on to monotherapy with metformin or in combination with multiple oral agents and insulin for patients with poorly controlled diabetes (21,24). In this study, greater efficacy was observed in the subgroup of patients who were not receiving an SU.…”
Section: Discussionmentioning
confidence: 62%
“…Overall, 29.3–64.5% [2832, 34, 36, 39, 42, 43, 45, 46, 48, 49, 5254, 5658, 70, 73] and 22.05–41.03% [28, 42, 45, 49, 52, 53, 56] patients with T2DM treated with liraglutide met the <7% and ≤6.5% HbA1c targets, respectively (for baseline characteristics of study population in these studies; see supplementary file 2).…”
Section: Resultsmentioning
confidence: 99%